m6A mRNA Methylation Regulates Epithelial Innate Antimicrobial Defense Against Cryptosporidial Infection - Xia, Zijie; Xu, Jihao; Lu, Eugene; He, Wei; Deng, Silu; Gong, Ai-Yu; Strass-Soukup, Juliane; Martins, Gislaine A.; Lu, Guoqing; Chen, Xian-Ming (Frontiers in Immunology, 2021)
Increasing evidence supports that N6-methyladenosine (m6A) mRNA modification may play an important role in regulating immune responses. Intestinal epithelial cells orchestrate gastrointestinal mucosal innate defense to microbial infection, but underlying mechanisms are still not fully understood. In this study, we present data demonstrating significant alterations in the topology of host m6A mRNA methylome in intestinal epithelial cells following infection by Cryptosporidium parvum, a coccidian parasite that infects the gastrointestinal epithelium and causes a self-limited disease in immunocompetent individuals but a life-threatening diarrheal disease in AIDS patients. Altered m6A methylation in mRNAs in intestinal epithelial cells following C. parvum infection is associated with downregulation of alpha-ketoglutarate-dependent dioxygenase alkB homolog 5 and the fat mass and obesity-associated protein with the involvement of NF-кB signaling. Functionally, m6A methylation statuses influence intestinal epithelial innate defense against C. parvum infection. Specifically, expression levels of immune-related genes, such as the immunity-related GTPase family M member 2 and interferon gamma induced GTPase, are increased in infected cells with a decreased m6A mRNA methylation. Our data support that intestinal epithelial cells display significant alterations in the topology of their m6A mRNA methylome in response to C. parvum infection with the involvement of activation of the NF-кB signaling pathway, a process that modulates expression of specific immune-related genes and contributes to fine regulation of epithelial antimicrobial defense.